Militer dan Politik di Indonesia dalam Konteks Ketegangan Maritim di Laut China Selatan - Sarlini, Heti; Yanti, Dewi; Santika, Serly; Hutabarat, Jelita Silvia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Maritime tensions in the South China Sea have become one of the most significant geopolitical issues in Southeast Asia. Indonesia, as a country with a strategic position in this region, plays a crucial role in these dynamics. This journal discusses the interaction between the military and politics in Indonesia in the context of the tensions in the South China Sea and how Indonesia responds to the increasing maritime security challenges in the area. Tensions in the South China Sea have intensified in recent years. As a maritime nation with strategic interests in the region, Indonesia plays a key role in maintaining stability and security in these conflict-ridden waters. This journal explores Indonesia's maritime political dynamics in the South China Sea, focusing on the domestic military and political aspects that influence Indonesia's policies and approaches to addressing these tensions. The South China Sea region has become a global focal point due to the intense territorial claims competition among neighboring countries. Indonesia, as the world's largest archipelagic state and a key player in Southeast Asia, has a strategic role in managing these maritime tensions. This article analyzes Indonesia's military and political dynamics concerning the maritime tensions in the South China Sea. The research employs document analysis and interviews with national security experts and relevant government officials. The findings indicate an enhancement of Indonesia's military capabilities, a foreign policy focused on maritime diplomacy, and Indonesia's active role in promoting peace and stability in the region.